Percutaneous Interventional Techniques for Treatment of Spinal Metastases - Tomasian, Anderanik; Jennings, Jack W. (Seminars in Interventional Radiology, 2020)
This article details an approach for evaluation as well as minimally invasive percutaneous treatment of spinal metastases focusing on thermal ablation and most recent advances. Safe and effective management of certain subgroups of patients with spinal metastases can be achieved by minimally invasive percutaneous thermal ablation with or without vertebral augmentation. Adjunctive palliative treatment options such as epidural or neuroforaminal corticosteroid and long-acting anesthetic injections may also be performed in patients who have nerve and radicular pain including those who are not candidates for thermal ablation. Thermal protection strategies should be implemented to minimize the risk of neural thermal injury.
Keywords: spinal metastases; thermal ablation; vertebral augmentation; pain palliation; local tumor control; interventional radiology